Pengaruh Audit Fee dan Audit Tenure Terhadap Kualitas Audit - Widiya Damayanti, Eka; Aufa, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The purpose of this study is to examine how to audit tenure and audit fees affect audit quality. This study employs secondary data types and a quantitative methodology. The annual reports of manufacturing firms in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016–2020 period serve as the research population. These reports are processed using a purposive sampling method based on predetermined criteria. Fifteen companies were chosen at random from the results of the specified criteria. Logistic regression analysis is used in this study. The survey's findings suggest that audit fees have a beneficial impact on audit quality. However, audit tenure does not affect audit quality.